노인요양시설 방역을 위한 시설 개선 방안 - 강지은; 권순정; 이현진 (의료·복지 건축, 2021)
Purpose: Senior long-term care facilities are vulnerable to a cluster infection because of frequent physical contact, large group dining, communal living, and room sharing. This study aims to provide architectural improvement plan for a quarantine system in the facilities. Methods: Actual quarantine action data, guidelines from governments and institutes, in-depth interviews with facility staff are analyzed. Results: To prevent a cluster infection in the senior facilities, it is necessary to provide an architectural plan focusing on increasing the number of single rooms and isolation rooms, providing isolation rooms for staff, separation of a soiled room from a clean room, planning an entry vestibule and a visitor’s room. Implications: It is important to analyze the existing condition of facilities that had been going through cohort isolation and provide the architectural solution to strengthen infection control.
Keywords: 코로나-19; 감염관리; 노인; 노인요양시설; 방역; 노인 시설; Covid-19; Infection control; Senior Facility; Elderly